2023
DOI: 10.3390/plants12081714
|View full text |Cite
|
Sign up to set email alerts
|

Studying Parameters Affecting Accumulation of Chilling Units Required for Olive Winter Flower Induction

Abstract: With global warming, mean winter temperatures are predicted to increase. Therefore, understanding how warmer winters will affect the levels of olive flower induction is essential for predicting the future sustainability of olive oil production under different climactic scenarios. Here, we studied the effect of fruit load, forced drought in winter, and different winter temperature regimes on olive flower induction using several cultivars. We show the necessity of studying trees with no previous fruit load as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Using this data, we attempted to develop a method for calculating CUs that correlated with the level of flower induction observed. We We found that all three models were successful in predicting the empirical flowering levels obtained under cold winters yielding high ๐‘–, but much less effective at predicting flowering levels under winters with warm periods in which low to moderate flowering levels were observed (Engelen et al, 2023). We attributed this lack of success under conditions marginal for flowering to the inherent limitation of this class of models, disregarding the dynamic process of temperature change throughout the winter.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Using this data, we attempted to develop a method for calculating CUs that correlated with the level of flower induction observed. We We found that all three models were successful in predicting the empirical flowering levels obtained under cold winters yielding high ๐‘–, but much less effective at predicting flowering levels under winters with warm periods in which low to moderate flowering levels were observed (Engelen et al, 2023). We attributed this lack of success under conditions marginal for flowering to the inherent limitation of this class of models, disregarding the dynamic process of temperature change throughout the winter.…”
Section: Introductionmentioning
confidence: 83%
“…Both the production rate ๐พ 0 (๐‘‡) and the decay rate ๐พ ๐‘ฅ (๐‘‡) of ๐‘ฅ are temperature-dependent. To ensure a bell-shaped temperature dependence of chilling accumulation, based on previous experiments (Engelen et al, 2023, Hartmann & Porlingis, 1957, we defined ๐พ 0 (๐‘‡) the production rate of ๐‘ฅ to be a Gaussian function with a maximum at the temperature known to be optimal for olive flowering (11 ๏‚ฐC)…”
Section: The Flowering Modelmentioning
confidence: 99%
See 3 more Smart Citations